Trusted computing: Challenges & solutions - Awang, Nor Fatimah (2009)
Most citizens of the world today are fighting for – either by battling viruses, spam, phishing or other malware, or by fending off schemes to compromise privacy and extract confidential information.With these worries in mind, the Trusted Computing Group (TCG) was established to develop specifications for trusted computing building blocks and software interfaces that could address the problems and aims to enhance security by using the transitive properties of trust. Unfortunately Trusted Computing is a young technology and struggling with some drawbacks. There are major issues related to technical as well commercial that need to be addressed seriously and carefully.From user’s perspective, TC was introduced from desire to prevent users from freely sharing and using potentially technology and seems will introduce more benefits to vendors and large corporations.The main legal concerns are copyright, anti-trust law, data privacy law and digital rights management, the impact on which are not yet clear. This paper will discuss the challenges that currently faced with Trusted Computing in all aspects from different perspective and at the same time provide several solutions to overcome the challenges.